2022
DOI: 10.1038/s41591-022-01942-9
|View full text |Cite
|
Sign up to set email alerts
|

Temporal order of clinical and biomarker changes in familial frontotemporal dementia

Abstract: Frontotemporal dementia (FTD), marked by impairments in behavior, language and sometimes motor function, is a common form of early-onset dementia 1 . Approximately 20-30% of FTD is caused by autosomal dominant mutations (familial, or f-FTD), usually in one of three genes: chromosome 9 open reading frame 72 (C9orf72), progranulin (GRN) or microtubule-associated protein tau (MAPT) 2 . FTD is uniformly fatal, and there are no approved therapies; however, a growing number of new treatments targeting C9orf72, GRN a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 63 publications
7
25
0
Order By: Relevance
“…Recent estimates suggest that f‐FTD clinical trials will require global recruitment to achieve sufficient power. 11 Decentralized trials may be necessary to overcome recruitment barriers and will require new tools to enable remote data collection.…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates suggest that f‐FTD clinical trials will require global recruitment to achieve sufficient power. 11 Decentralized trials may be necessary to overcome recruitment barriers and will require new tools to enable remote data collection.…”
Section: Introductionmentioning
confidence: 99%
“…Data from progranulindeficient mouse models indicates that progranulin-boosting therapeutics can correct behavioral, biochemical, and neuropathological abnormalities even after onset, but initiating treatment after symptoms emerge would be limited by the fact that FTD-GRN progresses rapidly once it becomes symptomatic. In disease progression models, FTD-GRN had the fastest decline among the three major genetic etiologies of FTD [151]. The ideal timeframe for treatment initiation is probably a few years before symptom onset, and identifying patients at this stage will likely be enabled by plasma biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Direct comparisons of these groups across the whole genetic FTD spectrum may, however, be limited because of considerable gene-related heterogeneity. 11,12,17,18 Variability in NfL longitudinal trajectories in individuals who convert appears related to the variant-carrying gene and partly to the clinical course. We found different trajectories of NfL levels in FTD genetic groups, characterized by a steep rapid increase after conversion in C9orf72, a steady increase in GRN, and a gradual increase followed by a plateau in MAPT, in line with previous research showing different NfL trajectories between genetic groups.…”
Section: Discussionmentioning
confidence: 99%
“…12 This time window is, however, too broad for clinical trials because these aim to recruit participants in closer proximity of symptom onset. Another large recent study found genotype-specific trajectories of biomarkers changes, including NfL, relative to estimated prodromal onset, 18 yet it had limited resolution on the clinical implications of these changes, such as their predictive and diagnostic value for the prodromal stage in the individual patient.…”
Section: Introductionmentioning
confidence: 99%